Novel Therapies for Parkinsonian Syndromes–Recent Progress and Future Perspectives - Przewodowska, Dominika; Marzec, Weronika; Madetko, Natalia (Frontiers in Molecular Neuroscience, 2021)
Background: Atypical parkinsonian syndromes are rare, fatal neurodegenerative diseases associ-ated with abnormal protein accumulation in the brain. Examples of these syndromes include pro-gressive supranuclear palsy, multiple system atrophy, and corticobasal degeneration. A common clinical feature in parkinsonism is limited improvement after levodopa. So far, there are no dis-ease-modifying treatments to address these conditions, and therapy is only limited to alleviating symptoms. Diagnosis is devastating for the patient as the prognosis is extremely poor and disease tends to progress rapidly. Currently, potential causes and neuropathological mechanisms involved in these diseases are being widely investigated. Objectives: The aim of this review is to summarize recent advances and gather emerging disease-modifying therapies that could slow the progression of atypical parkinsonian syndromes. Methods: PubMed and Google Scholar databases were searched regarding novel perspectives for atypical parkinsonism treatment. The following medical subject headings were used: ‘atypical parkinsonian syndromes – therapy’, ‘treatment of atypical parkinsonian syndromes’, ‘atypical parkinsonian syndromes – clinical trial’, ‘therapy of tauopathy’, ‘alpha-synucleinopathy treat-ment’, ‘PSP therapy/treatment’, ‘CBD therapy/treatment, ‘MSA therapy/treatment’, and ‘atypical parkinsonian syndromes – disease modifying’. All search results were manually reviewed prior to inclusion in this review. Results: Neuroinflammation, mitochondrial dysfunction, microglia activation, proteasomal im-pairment, and oxidative stress play a role in the neurodegenerative process. Ongoing studies and clinical trials target these components in order to suppress toxic protein accumulation. Various approaches such as stem cell therapies, anti-aggregation/anti-phosphorylation agent administra-tion, or usage of active and passive immunization appear to have promising results. Conclusion: Presently, disease-modifying strategies for atypical parkinsonian syndromes are be-ing actively explored with encouraging preliminary results. This leads to an assumption that de-veloping accurate, safe, and progression-halting treatment is not far off. Nevertheless, further in-vestigation remains necessary.